PENGARUH LATIHAN BERSYARAT GERAKAN DENGAN JATUH, MENYELAM DAN MELAYANG TERHADAP PENINGKATAN WAKTU REAKSI PENJAGA GAWANG SEKOLAH SEPAKBOLA UNIVERSITAS RIAU DAN SEKOLAH SEPAK BOLA PEKANBARU CITY SOCCER SCHOOL U-17 - Julianto, Igo; Zainur, Zainur; Mandan, Ali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstark: The problem raised in this research is that there is a lack of responses in anticipating the arrival of the ball. Imperfectperformance for goalkeepers when playing games or football matches is not optimal. The purpose of this research is to determine the reaction speed of the goalkeeper. The format of this research is (using a one-group pre-test-post-test design approach) with a population of goalkeepers from Riau University football school and U-17 city football school Pekanbaru. The data in this research refer to the entire population, namely 6 persons. The instrument used in this research was the whole body reaction test, which aims to determine the effect of the reaction rate. The data was then statistically processed to test for normality using the Lilifours test at a significant level of 0.05α. Based on the analysis of the normality test, the X data produces LoMaks of 0.198 and Ltable of 0.319. while variable Y yields LoMaks of 0.254 and an L table of 0.319. This means LoMaks<Ltable, then the data will be distributed normally. Based on the statistical data analysis of the t-distribution test, the t-count is 4.378 and the t-table is 2.015. Thus, there is an effect of conditional movement training with falling, diving and hovering on the increase in the reaction time of goalkeepers at Riau University Football School and U-17 Pekanbaru City Soccer School.Key Words: Motion Conditional Training with falls, Diving and Gliding,Reaction Time, Football